1995
DOI: 10.1111/j.1365-2796.1995.tb00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating autoantibodies as serological markers in the differential diagnosis of pulmonary renal syndrome

Abstract: Our study demonstrated that the presence of autoantibodies is a predominant feature of PRS and that the type of immunologic injury is of paramount importance in determining the course of illness in this syndrome. Analysis of the aforementioned antibodies can help in an early differential diagnosis and thus, in better management of PRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
20

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 23 publications
0
40
0
20
Order By: Relevance
“…The duration of respiratory symptoms before hospital admission is a predictive factor. Previous studies have shown that DAH often occurs as a slow, evolving process in vasculitis [10,33]. In contrast, DAH frequently has a sudden onset in SLE [7].…”
Section: Discussionmentioning
confidence: 99%
“…The duration of respiratory symptoms before hospital admission is a predictive factor. Previous studies have shown that DAH often occurs as a slow, evolving process in vasculitis [10,33]. In contrast, DAH frequently has a sudden onset in SLE [7].…”
Section: Discussionmentioning
confidence: 99%
“…The rapid availability of these antibodies has improved the time to establish an early diagnosis, which is prognostically relevant [Saxena 1995]. …”
Section: Diseasementioning
confidence: 99%
“…The differential diagnosis of pulmonary-renal syndrome is even more limited with 65-80% of cases resulting from either WG, MPA, or Goodpasture syndrome (GS). [13][14][15] Chest imagingfindings of cavities or nodules As the SVV mimic vastly more common entities such as pneumonia or ARDS, the key to diagnosis is to note features that are inconsistent with the natural history …”
Section: -12mentioning
confidence: 99%